If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + 32 = 6z + -2 Reorder the terms: 32 + 4z = 6z + -2 Reorder the terms: 32 + 4z = -2 + 6z Solving 32 + 4z = -2 + 6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6z' to each side of the equation. 32 + 4z + -6z = -2 + 6z + -6z Combine like terms: 4z + -6z = -2z 32 + -2z = -2 + 6z + -6z Combine like terms: 6z + -6z = 0 32 + -2z = -2 + 0 32 + -2z = -2 Add '-32' to each side of the equation. 32 + -32 + -2z = -2 + -32 Combine like terms: 32 + -32 = 0 0 + -2z = -2 + -32 -2z = -2 + -32 Combine like terms: -2 + -32 = -34 -2z = -34 Divide each side by '-2'. z = 17 Simplifying z = 17
| x^2-9x+36=0 | | 5(x-6)=3x-14 | | 35x^2+42x+12=0 | | 4x^2=2x-5 | | 6z-2+2z+16=90 | | 6z-2=2z+16 | | 2z+16=6z-2 | | 239-3x=42x+19 | | (10x+5)(x-9)=0 | | 83-4x=41x+23 | | 123-5x=2x+18 | | (5-y)+(6-7)-(5-y)=0 | | x(4)=-6 | | t^2+17=-8t | | 71-7x=2x+20 | | 7-6x=139-37x | | 2x+3x-12x= | | 4x+8=-80-7x | | -12-4x=13-4x | | 63-2x=2x+19 | | 8x-6=7x+3 | | -31-2x=2x+19 | | q-(5-q)3=-7 | | 6x+34=15x-38 | | 2x+32=11x-58 | | 18x^3-6x^2+8x= | | 16x^2-9y^2= | | 2(x-5)=11 | | 2(x-5)=-11 | | 5*8+9-6*5=10 | | -1(6-3x)=-3 | | -5x-2(6-3x)=13 |